2009
DOI: 10.1080/00076790902726582
|View full text |Cite
|
Sign up to set email alerts
|

Transactions, standardisation and competition: Establishing uniform sizes in the British wire industry c.1880

Abstract: When science could not provide a solution to transaction problems in the British wire industry c.1880, market groups had to negotiate a business solution. This involved converging towards a 'one-size-fits-all' standard: a process requiring compromises and cooperation between competitive firms, and solving coordination failure through state intervention. This paper demonstrates how different groups held different notions of 'ideal' standards depending on the incentives they faced. Reconciling these differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…62 Yet achieving convergence on standards often required negotiation and conciliation between competing interests. 63 As early as 1775, raw cotton in England began to be categorized by its place of growth, such as American, Indian, or West Indian. It is suggested that Joshua Holt attempted the first systematic grading of cotton in England around 1775.…”
Section: Institutional Solutions: Evidence Of Market Coordination In the Liverpool Cotton Marketmentioning
confidence: 99%
“…62 Yet achieving convergence on standards often required negotiation and conciliation between competing interests. 63 As early as 1775, raw cotton in England began to be categorized by its place of growth, such as American, Indian, or West Indian. It is suggested that Joshua Holt attempted the first systematic grading of cotton in England around 1775.…”
Section: Institutional Solutions: Evidence Of Market Coordination In the Liverpool Cotton Marketmentioning
confidence: 99%
“…Faced with the need for substantial capital investment to secure connectivity, reduce duplication and enforce standards, cooperation was required in the banking community to create and operate a network for collective benefit. This was achieved very successfully through an unusual crossborder not-for-profit organisation in which participants co-operated to produce a standardised solution, a topic addressed recently in this journal in a very different context by Velkar (2009). The authors explain how this success came about and address concerns that it has constrained competition and innovation.…”
Section: The Articlesmentioning
confidence: 99%
“…Dobraszczyk argues for the importance of forms in the development of the information state, presenting a case study of the design of census schedules and their reception by the public in the nineteenth century. Industrial standardization was a theme pursued in studies of the British wire industry (Velkar) and British and American mechanical engineering (Kershaw). There were several articles with an environmental dimension.…”
Section: (V) 1850–1945
Kate Bradley and James Taylor
University Of Kementioning
confidence: 99%